1996
DOI: 10.1111/j.1365-2249.1996.tb08309.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of IL-6 by T cells from the femoral head of patients with rapidly destructive coxopathy (RDC)

Abstract: SUMMARYRDC is a syndrome with unknown etiology that causes rapid destruction of a hip joint. We have investigated the production of osteoclast-activating cytokines (IL-6, IL-la and tumour necrosis factor-alpha (TNF-a)), interferon-gamma (IFN-y) and IL-8 by T cells in the affected joint. The level of IL-6 produced by the T cell lines (TCL) established from the femoral head was significantly higher than that from patients' or healthy donors' peripheral blood mononuclear cells (PBMC). IL-6 production by the TCL f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Pathologically, many investigators have reported that osteoclast count is significantly greater in active areas of the hip in RDHD than in osteoarthritic patients along with vascular-rich granulation, suggest ing that vascularity is an important factor in the osteolysis and destruction of the bone [ 14 , 15 ]. Others have demonstrated elevated levels of interleukin-6 (IL-6), IL-1β in the joint fluid of affected patients as well as increased secretion of matrix metalloproteinases(MMP) by fibroblasts from the affected synovium and subchondral cysts [ 16 , 17 ]. Although implicated as a causative factor, no genetic analysis such as that using human leukocyte antigen for rapidly destructive arthropathy has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, many investigators have reported that osteoclast count is significantly greater in active areas of the hip in RDHD than in osteoarthritic patients along with vascular-rich granulation, suggest ing that vascularity is an important factor in the osteolysis and destruction of the bone [ 14 , 15 ]. Others have demonstrated elevated levels of interleukin-6 (IL-6), IL-1β in the joint fluid of affected patients as well as increased secretion of matrix metalloproteinases(MMP) by fibroblasts from the affected synovium and subchondral cysts [ 16 , 17 ]. Although implicated as a causative factor, no genetic analysis such as that using human leukocyte antigen for rapidly destructive arthropathy has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Among several kinds of multinuclear giant cells, osteoclast cells can be characteristically identified as the multinuclear cells within the indentations of the bone matrix . Histopathologically, HE staining has also reportedly revealed the presence of many osteoclast‐like multinuclear giant cells at the center of the bone destruction in RDA . In reference to these reports, the number of multinuclear giant cells along the trabecular bone at the subchondral bone region per mm 2 was calculated using a mid‐coronal slice of all histopathological specimens (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Mature and activated osteoclasts occur in the synovial membrane and granulomatous bone marrow lesions occur in the focal destructive portion of the femoral heads [11]. Femoral head bone resorption is brought about through the production of IL-6 in RDC hips [12]. Osteoclast cells also occur at the reparative zone of the collapsed femoral head in hips with osteonecrosis (ON) of the femoral head [13].…”
Section: Introductionmentioning
confidence: 99%